Who Knows, Who Cares? Dementia knowledge among nurses, care workers, and family members of people living with dementia - Robinson, A.; Eccleston, C.; Annear, M.; Elliott, K.; Andrews, S.; Stirling, C.; Ashby, M.; Donohue, C.; Banks, S.; Toye, Christine; McInerney, F. (Centre for Bioethics, IRCM, 2014)
The number of people with dementia is increasing rapidly worldwide. Commensurate with population ageing, the use of nursing homes in Australia (known as residential aged care facilities) for individuals with dementia is growing. As a terminal condition, dementia is best managed by instituting a palliative approach to care. A good knowledge of dementia, including its progression and management, among staff and families of people living with dementia is essential for clear decision making and the provision of appropriate care. Yet there is limited information regarding relative levels of dementia knowledge. This paper reports the results of a study that assessed dementia knowledge among these two cohorts using the Dementia Knowledge Assessment Tool; the study surveyed 279 staff members and 164 family members of residents with dementia. Dementia knowledge deficits were evident in both cohorts across a range of areas. It is critical that dementia knowledge deficits are identified and addressed in order to support evidence-based dementia care.